Multicompartmental Scaffolds for Coordinated Periodontal Tissue Engineering. (November 2022) - Yao, Y.; Raymond, J.E.; Kauffmann, F.; Maekawa, S.; Sugai, J.V.; Lahann, J.; Giannobile, W.V.
Successful periodontal repair and regeneration requires the coordinated responses from soft and hard tissues as well as the soft tissue–to–bone interfaces. Inspired by the hierarchical structure of native periodontal tissues, tissue engineering technology provides unique opportunities to coordinate multiple cell types into scaffolds that mimic the natural periodontal structure in vitro. In this study, we designed and fabricated highly ordered multicompartmental scaffolds by melt electrowriting, an advanced 3-dimensional (3D) printing technique. This strategy attempted to mimic the characteristic periodontal microenvironment through multicompartmental constructs comprising 3 tissue-specific regions: 1) a bone compartment with dense mesh structure, 2) a ligament compartment mimicking the highly aligned periodontal ligaments (PDLs), and 3) a transition region that bridges the bone and ligament, a critical feature that differentiates this system from mono- or bicompartmental alternatives. The multicompartmental constructs successfully achieved coordinated proliferation and differentiation of multiple cell types in vitro within short time, including both ligamentous- and bone-derived cells. Long-term 3D coculture of primary human osteoblasts and PDL fibroblasts led to a mineral gradient from calcified to uncalcified regions with PDL-like insertions within the transition region, an effect that is challenging to achieve with mono- or bicompartmental platforms. This process effectively recapitulates the key feature of interfacial tissues in periodontium. Collectively, this tissue-engineered approach offers a fundament for engineering periodontal tissue constructs with characteristic 3D microenvironments similar to native tissues. This multicompartmental 3D printing approach is also highly compatible with the design of next-generation scaffolds, with both highly adjustable compartmentalization properties and patient-specific shapes, for multitissue engineering in complex periodontal defects.